2017
DOI: 10.2174/1381612823666170207145420
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Modulation and Anti-Inflammatory Properties of Dietary Polyphenols in IBD: New and Consolidated Perspectives

Abstract: In this review, we will focus on the dietary flavonols, anthocyanins and stilbenes, as widely occurring polyphenols in human diet, their metabolism mediated by gut microbiota and their protective effects on inflammatory bowel diseases (IBDs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 2 publications
1
34
0
Order By: Relevance
“…In healthy individuals, the mucosal immune system is dynamically educated towards tolerance to luminal antigens, including commensal bacteria and food derived antigens [ 35 ]. Several factors contribute to DCs’ “maturation” [ 23 , 24 ], including food-derived products [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…In healthy individuals, the mucosal immune system is dynamically educated towards tolerance to luminal antigens, including commensal bacteria and food derived antigens [ 35 ]. Several factors contribute to DCs’ “maturation” [ 23 , 24 ], including food-derived products [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…On these bases, their consumption might have positive effects on human health. Other studies indicate that diets rich in anthocyanins and phenolic acids have protective effects against oxidative stress, involved in the onset of aging processes and several human pathologies [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…In plants, anthocyanins are synthetized by the flavonoid biosynthetic pathway, which leads also to the production of phenolic acids and other classes of polyphenols with healthy benefits [20][21][22]. In this study, we carried out the chemical profiling of antioxidant compounds and characterized the main classes of polyphenols, carotenoids, sugars, and organic acids, which can contribute to the quality and nutritional value of Tiggiano carrots and to the valorization of this local landrace.…”
Section: Introductionmentioning
confidence: 99%
“…Canarium album is a type of polyphenol-rich fruit with a total phenolic content of 1174.0–1799.6 mg gallic acid equivalents/100 g fresh weight [ 11 ]. Its high polyphenol content is related to hepatoprotective [ 12 ], antioxidant [ 13 ], anti-inflammatory [ 14 ], and antiviral [ 15 ] effects. We previously found that polyphenol-rich Canarium album extract (CAext) restrains excessive lipid accumulation induced by oleic acid in hepatocarcinoma cells [ 16 ].…”
Section: Introductionmentioning
confidence: 99%